French books of hours making an archive of prayer, c. 1400-1600 - Reinburg, Virginia (Cambridge ; New York : Cambridge University Press, 2012)
"The book of hours was a 'best-seller' in medieval and early modern Europe, the era's most commonly produced and owned book. This interdisciplinary study explores its increasing popularity and prestige, offering a full account of the book of hours as a book - how it was acquired, how it was read to guide prayer and teach literacy and what it meant to its owners as a personal possession. Based on the study of over 500 manuscripts and printed books from France, Virginia Reinburg combines a social history of the book of hours with an ethnography of prayer. Approaching the practice of prayer as both speech and ritual, she argues that a central part of the book of hours' appeal for lay people was its role as a bridge between the liturgy and the home. Reinburg describes how the book of hours shaped religious practice through the ways in which it was used"--
"The book of hours is one of the most familiar relics of medieval and early modern Europe. Libraries, museums, and private collectors around the world own thousands of them. That number represents but a fraction of all the books of hours created between 1250 and 1600. Many were destroyed over the intervening centuries of war, natural disaster, and religious change, not to mention the mundane ravages of time. Still, the survival of so many examples and the diversity of their contents make the book of hours an ideal source for exploring the history of art, religion, and the book. Scholars have lavished attention on books of hours. Art historians write about the books' fabrication, illustration, and patronage. Literary scholars and historians shed light on texts, prayers, and readership. Abundant scholarship on the book of hours has helped to make it the best known artifact of medieval and early modern culture"--
Machine generated contents note: Introduction; Part I. A Social History of the Book of Hours: Prologue to Part I; 1. Culture and commerce; 2. Owners and their books; 3. Prayer book and primer; Part II. An Ethnography of Prayer: Prologue to Part II; 4. Words and rites; 5. A fragment of a religion; 6. Prayer to the Virgin Mary; Conclusion; Bibliography.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Books of hours -- France; Books and reading -- Social aspects -- France -- History; HISTORY / Europe / General; RELIGION / Christian Life / Devotional; RELIGION / Devotional; Electronic books